THE IMPLEMENTATION OF STORYTELLING TECHNIQUE IN SPEAKING SKILL FOR ISLAMIC SENIOR HIGH SCHOOL STUDENTS - Rizkiyah Khoirin Nawa (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2023)
This study aimed to describe the implementation of storytelling on students' speaking skills. The method used in this study is qualitative descriptive, with the object of a teacher and students of class X MA Assalam Senior High School. The Instruments of this study are observation and interview. The researcher used observation and interviews with the teacher to collect the data to answer the first research questions. The researcher also interviewed the teacher to get additional information. Then, the researcher conducted the interview with five students to answer the second research question. The findings of the observations and interviews are almost the same as the step in Jianing's methods, such as choosing the content, separating students into various groups, evaluating the student's performance, and delivering them some feedback at the end of the meeting. The teacher explained that applying storytelling technique in teaching speaking makes students more interested in learning English because they learn about descriptive text. Moreover, the storytelling technique is positively received by most students. The interview with five students showed that students actively participated during teaching activities. It could be concluded that storytelling techniques improved students' vocabulary, confidence, and enjoyment of studying English.